Effect of spirulina (Arthrospira platensis) supplementation on tilapia (Oreochromis niloticus) growth and stress responsiveness under hypoxia - Plaza, Ignacio; Garcia, José L.; Villarroel, Morris (Spanish Journal of Agricultural Research, 2018)
Several recent studies have shown that Arthrospira sp. supplementation of feeds has a beneficial effect on fish health and growth, but less is known about its possible effects on stress responsiveness. The present study was designed to evaluate using Arthrospira platensis as a feed supplement for Oreochromis niloticus fry, reared in recirculating aquaculture systems. Two isocaloric and isonitrogenous fishmeal-based diets were prepared with 0% and 1% A. platensis and fed to fry, approximately 10 mg live weight at the beginning of the experimental period (n=16 tanks, 8 tanks per treatment), at a feeding rate of 6% live weight, four meals a day for 50 d. The weight gain per tank, specific growth rate and feed conversion ratio were similar among treatments but A. platensis supplementation significantly increased survival (p<0.05). Stress responsiveness was measured in all fish from 12 tanks using a non-invasive two-choice test. All fish from one home tank (n=6 tanks per treatment), were placed into a shaded tank where oxygen levels were slowly reduced. A doorway was then opened to a second illuminated tank with normal oxygen levels and the number of fish that left the home tank were counted. The fish fed A. platensis stayed significantly (p=0.001) longer in the home tank (30.20 min ± 13.22) than controls (17.35 min ± 8.32), suggesting a lower stress responsiveness and a higher tolerance to hypoxia.